The Effect of Copper-Silver (Cu-Ag) Double Doping on ZnO Photoanode on Dye Sensitized Solar Cell (DSSC) Efficiency - Berliani, Rhiska Aria; Haq, Fat Hana Rizqi; Ningrum, Eka Silvia; Lestari, Putri; Iriani, Yofentina; Nurosyid, Fahru (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2024)
A DSSC has a good performance seen from the ability of the photoanode to absorb sunlight. The use of photoanodes uses a semiconductor material, namely ZnO. However, in use, ZnO has the disadvantage of low optical and electrical properties, which results in low DSSC efficiency. So in this research, efforts are made to add Cu-Ag double doping to improve optical and electrical properties that will increase the efficiency of DSSC. ZnO/Cu-Ag photoanodes were prepared using the sol-gel spin coating method with doping variations of 0%, 1%, 2%, and 3%. Characterization was carried out using a UV-Vis spectrophotometer to see the absorption area and determine the band gap energy of the ZnO photoanode. I-V Keithley was used for current and voltage characterization to determine the conductivity of the ZnO photoanode and the efficiency of the DSSC. The results of the research show the effect of increasing the optical properties of ZnO photoanodes by decreasing the band gap energy along with the increase in doping concentration, namely 3.29 eV, 3.24 eV, 2.44 eV, and 2.40 eV. In addition, there is an increase in conductivity on the ZnO photoanode with the highest conductivity at doping concentration of 3% which is 0.1006 Ω-1m-1 with an increase of 6 times compared to the pure ZnO photoanode of 0.0163 Ω-1m-1. The improved optical and electrical properties of ZnO/Cu-Ag photoanodes have an impact on increasing the efficiency value of DSSC with the optimum efficiency achieved at 1% doping concentration of 0.0291% with an increase of 16 times compared to the use of pure ZnO photoanode of 0.00018%. The addition of Cu-Ag doping to ZnO improves the optical and electrical properties of the photoanode, enhancing DSSC efficiency with an optimum at 1% doping concentration.